Prolonged repeated inseminations trigger a local immune response and accelerate aging of the uterovaginal junction in turkey hens - Kosonsiriluk, Sunantha; Reed, Kent M.; Noll, Sally L.; Wileman, Ben W.; Studniski, Marissa M.; Boukherroub, Kahina S. (Frontiers in Physiology, 2023)
Artificial insemination is a standard practice in the turkey breeder industry to ensure the production of fertile eggs. Even though hens are inseminated on a weekly basis, their fertility tends to decline after a few weeks of production. Avian species have a specialized structures called sperm storage tubules (SSTs), located in the uterovaginal junction (UVJ) of the oviduct. The ability of SSTs to store sperm is directly correlated with the fertility of the hen. The objective of the study was to examine changes in the transcriptome of the turkey hen’s UVJ in response to the presence of sperm at three key stages of production. We hypothesized that repeated and prolonged exposure to sperm would alter the transcriptome of the UVJ. Samples were collected from virgin hens prior to the onset of lay, as well as from sham-inseminated (extender only) and semen-inseminated hens at early lay, peak lay, and late lay. Gene expression profiling of the UVJ was examined, and a differential expression analysis was conducted through pairwise comparisons between semen- and sham-inseminated groups at each production stage and across production stages. In the early laying stage, no significant gene expression changes were found between semen- and sham-inseminated groups. However, at peak lay, genes related to lipid biosynthesis, Wnt signaling, cell proliferation, and O-glycan biosynthesis were up-regulated in the semen group, while the immune response and cytokine-cytokine receptor interaction were down-regulated. In the late lay stage, the transcription pathway was up-regulated in the semen group, whereas the translation pathway was down-regulated. The local immune response that was suppressed during peak lay was increased at the late laying stage. In the semen-inseminated group, the UVJ exhibited advanced aging at the late laying stage, evidenced by reduced telomere maintenance and translation processes. The results from this study provide valuable insights into the alteration of the UVJ function in response to the presence of sperm at different stages of production and throughout the production cycle. Targeting the modulation of local immune response and addressing aging processes after peak production could potentially prevent or delay the decline in fertility of turkey breeder hens.